Synthesis of Al-Doped ZnO films assisted with hollow-cathode glow discharge and their characterization - Feitor, Michelle Cequeira (2021)
Transparent conductive oxides, such as aluminum-doped zinc oxide (AZO), are of substantial importance for use in a broad range of applications because of their excellent optical and electrical properties. AZO film can be deposited by using several conventional techniques, although they suffer from limitations such as long deposition time, high cost, and the requirement for complex deposition equipment. Here, we used hollow-cathode glow discharge, which produces a high-density plasma and achieves high deposition efficiency. Remarkably, instead of metallic target materials, we used Al2O3 and ZnO powders filled in the hollow cathode as a target, thus avoiding the need for specifically designed targets in this technique. The films were deposited using mixtures of argon and oxygen at various ratios (0% to 50% oxygen), to improve the film characteristics. The films deposited under all conditions exhibited hexagonal wurtzite ZnO structure, while the grain size increased with increasing oxygen content. The film was thick and porous when using low oxygen content, but became thin and dense with increasing oxygen content. The optical transmittance was found to be strongly dependent on the processing gases used, with the highest transmittance of 84% being attained when using 25% oxygen gas. The bandgap of the films lay between 3.27 eV and 3.33 eV. The highest carrier concentration and mobility were attained when using 25% oxygen, and the Hall resistivity decreased with increasing oxygen content. Besides the excellent transmittance and electrical properties of the deposited films, it is expected that the results of this study will be useful for solar cells and optoelectronic applications due to the relatively low cost of this technique and the lack of specific target requirements